A Distinctive Indian Political Economy: New Concepts and a Synthesizing Framework. (December 2016) - Sinha, Aseema
This article discusses Rudolphs' contribution to the study of India's political economy. Taking off from the ideas they presented in their work, In Pursuit of Lakshmi, the article argues that certain concepts, such as Bullock capitalists, demand-led growth, involuted pluralism, federal market economy and state as a third actor, continue to be critical in understanding India. Through these conceptual innovations, Rudolph and Rudolph not only analyzed India at a given moment but also shaped the larger agenda of debates over India's political economy.